Strong and radiative decays of heavy flavored baryons; Physical Review D; Vol. 80, iss. 9 - Ivanov M. A.; Korner J. G.; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich; Rusetsky A. G. (1999, 1999)
Title screen